The mediating effect of geospatial thinking on the relationship between family capital and sense of place - Zhang, Jianzhen; Liang, Xiaoyu; Su, Ting; Li, Xinyao; Ge, Jiahao; An, Zhenni; Xu, Yanhua (Frontiers in Psychology, 2022)
Few studies have examined how family capital affects the sense of place, and the effect of spatial thinking on the relationship between the two is unclear. This study constructs a mediation model to examine the impact of family capital on sense of place and the mediation effect of geospatial thinking. A total of 1,004 upper-secondary-school students were surveyed using the Family Capital Questionnaire, the Geospatial Thinking Test, and the Sense of Place Scale. The correlation analysis showed that family capital has a positive effect on both sense of place and geospatial thinking. Moreover, there is also a significant positive correlation between geospatial thinking and sense of place. The results of mediation analysis indicated that geospatial thinking plays mediating and buffering roles in the relationship between family capital and sense of place after controlling for gender and residential address. The direct and indirect effects accounted for 73.31 and 26.69% of the total effect, respectively. Specifically, family capital is a significant positive predictor of both sense of place and geospatial thinking, and geospatial thinking partially mediates the relationship between family capital and sense of place. Students from better family backgrounds are more likely to have a better geospatial thinking and sense of place, as well as geospatial thinking promotes the development of a sense of place. Therefore, both family capital and geospatial thinking should be considered when we want to examine and develop individuals’ level of sense of place.